EMPLOYEES PERCEPTIONS ON THE RESILIENCE STRATEGY OF NATIONAL HOSPITAL IN SURABAYA IN FACING THE ECONOMIC CRISIS AS THE IMPACT OF THE COVID-19 PANDEMIC - Wendy Miharja; Soegeng Wahyoedi; Melitina Tecoalu (RADJA PUBLIKA, 2022)
Based on the background of the post-COVID-19 pandemic, which has not completely subsided and the global economic situation which has resulted in slow economic recovery and can threaten the sustainability of the company, the research problem is formulated as follows: “How do employees perceive the company's resilience strategy that has been implemented in the face of the economic crisis? as a result of the COVID-19 pandemic?” This research was conducted with the aim of understanding the strategies implemented by companies in maintaining business resilience in the face of the economic crisis as a result of the COVID-19 pandemic. So that the purpose of this study can be described to determine employee perceptions of the company's resilience strategy that has been implemented in the face of the economic crisis as a result of the COVID-19 pandemic. This study uses a qualitative descriptive method by conducting interviews where research participants are employees who have worked at least three years in the company or have worked at the company during the COVID-19 pandemic.